Pengaruh Gaya Kepemimpinan dan Budaya Organisasi terhadap Loyalitas Pengurus Himpunan Pelajar Mahasiswa Indonesia Parepare Komisariat Univeritas Negeri Makassar - Rukma Inna; Ilham Wardhana H; Burhanuddin Burhanuddin; Zainal Ruma; Rezky Amalia Hamka (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2026)
This study aims to determine the influence of leadership style and organizational culture on the loyalty of the HIPMI Parepare Commissariat, Makassar State University (UNM) administrators. The research variables consist of leadership style as the first independent variable (X₁), organizational culture as the second independent variable (X₂), and administrator loyalty as the dependent variable (Y). The study population was all 40 active HIPMI Parepare Commissariat administrators at UNM during the study period. The sampling technique used was saturated sampling (census), thus the entire population was included as respondents. Data were obtained through questionnaires and analyzed using multiple linear regression with the help of SPSS. The results show that leadership style has a positive and significant effect on administrator loyalty, organizational culture has a positive and significant effect on administrator loyalty, and simultaneously, both leadership style and organizational culture have a significant effect on administrator loyalty. These findings indicate that the more effective the leadership style implemented and the stronger the organizational culture developed, the higher the level of administrator loyalty to the organization. The synergy between participatory leadership and a healthy organizational culture can create a conducive organizational environment, increase commitment, and strengthen organizational sustainability.